Valoración de las tendencias sobre el consumo de productos alimenticios de origen orgánico en el sector "La Floresta", parroquia Mariscal Sucre del Distrito Metropolitano de Quito. - León Cevallos, Samantha Isabel (2015)
At the present organic products have become important inside the costumer’s minds, so it’s necessary to make an investigation in order to identify market trends, people need to know which one of those is the most important and what have led to a change of mentality. In the parish Mariscal Sucre is La Floresta, considered an area of great history and a bohemian neighborhood for all the activities that take place there, in La Floresta there is a great activity in terms of marketing of organic food products and various fairs that are held on weekends. A sample of 93 people was took, which has conducted a survey, with this we could evidence all kind of socioeconomic conditions of the families who live in the area and we also appreciate the level of consumption of organic products, what group of organicfoods are the main products consumed, the reasons why people started consuming those products and the reasons why people who doesn’t consume would start consuming. The highlight of this research is the assessment that was carried out with existing consumer trends, you can clearly see a large increase in the interest of people for their health and how some traditional trends do not affect most people.